The influence of political bias in state pension funds - Bradley, Daniel; Pantzalis, Christos; Yuan, Xiaojing (Journal of Financial Economics, 2016)
Using a sample of state pension funds’ equity holdings, we find evidence of not only local bias, but also bias towards politically-connected stocks. Political bias is detrimental to fund performance. State pension funds have longer holding durations of politically-connected local firms and display disposition behavior in these positions. Political bias is positively related to the percentage of politically-affiliated trustees on the board and Congressional connections. The more politically-affiliated trustees on the board, the more the fund shifts toward risky asset allocations. Overall, our results imply that political bias is likely costly to taxpayers and pension beneficiaries.